Sclerobanding in the treatment of second and third degree hemorrhoidal disease in high risk patients on antiplatelet/anticoagulant therapy without suspension: a pilot study - Pata, Francesco; Bracchitta, Luigi M.; Nardo, Bruno; Gallo, Gaetano; D’Ambrosio, Giancarlo; Bracchitta, Salvatore (Frontiers in Surgery, 2023)
Introduction: Around 20% of population in western countries is under anticoagulant treatment. However, there is paucity of evidence in the treatment of HD in patients under anticoagulant/antiplatelet therapy, although both suspension and continuation in the perioperative period may increase the risk of severe complications. The aim of this pilot study is to confirm the feasibility and safety of sclerobanding (Combined Rubber Band Ligation with 3% Polidocanol Foam Sclerotherapy), an office-based procedure, for the treatment of second-and third-degree HD in patients under anticoagulant/antiplatelet therapy without suspension. Materials and methods: Patients affected by second-third-degree haemorrhoids unresponsive to conservative treatment and under anticoagulant/antiplatelet were enrolled between November 2019 and October 2021. Postoperative complications, readmission, mortality and reintervention during the follow-up were evaluated. Results: Fifty-one patients were recruited, 23 female (45.1%) and 28 male (54.9%), with an average age of 65 years ± 11.4 SD (range 42-90). Twenty-seven patients (52.9%) had II-degree haemorrhoidal disease, and 24 (47.1%) had grade III-degree. while the most frequently taken medications were dual antiplatelet therapy (51%) and new oral anticoagulants (NOACs) (21.6%). The mean follow-up was 23 months. No intraoperative complications were recorded. The rate of complications in the first postoperative month was 13.7%, represented by mild complications: 6 This is a provisional file, not the final typeset article cases of moderate to severe pain and 1 case (2%) of thrombosis of a residual haemorrhoidal nodule, all regressing after conservative therapy. No severe complications were reported. Postoperative complications were not statistically significantly associated with the number of nodules treated (1, 2, or 3), the disease grade(2nd vs. 3rd) or the specific anticoagulant/antiplatelet regimen. During follow-up, 2 patients (4%) required a new procedure for recurrent bleeding: one an infrared photocoagulation as outpatient, and another a haemorrhoidectomy after 3 months. No cases of intraoperative or postoperative mortality occurred. Conclusions: Sclerobanding is a safe and effective technique in treating intermediate-grade haemorrhoidal disease in patients at high risk on anticoagulant/antiplatelet therapy. Sclerobanding is repeatable, usually does not require anaesthesia, and is cost-effective. Observational multicentre studies with a larger number of patients and controlled clinical trials will be needed to confirm these results.